Amnesties, accountability, and human rights - Jeffery, Renée (Pennsylvania studies in human rights., 2014)
"Amnesties, Accountability, and Human Rights examines why and how amnesties persist in the face of mounting pressure to prosecute the perpetrators of human rights violations. Drawing on more than 700 amnesties instituted between 1970 and 2005, Renée Jeffery maps out significant trends in the use of amnesty and offers a historical account of how both the use and the perception of amnesty has changed. As mechanisms to facilitate transitions to democracy, to reconcile divided societies, or to end violent conflicts, amnesties have been adapted to suit the competing demands of contemporary postconflict politics and international accountability norms. Through the history of one evolving political instrument, Amnesties, Accountability, and Human Rights sheds light on the changing thought, practice, and goals of human rights discourse generally."--Publisher website.